Therapy targeted to the NLRP3 inflammasome in chronic kidney disease - Yong Ji; Hu Hua; Zhanjun Jia; Aihua Zhang; Guixia Ding (Karger Publishers, 2024)
Background: The NLRP3 inflammasome is a cytoplasmic polymeric protein complex composed of the cytoplasmic sensor NLRP3, the apoptosis-related spot-like protein ASC, and the inflammatory protease caspase-1. NLRP3 activates and releases IL-1β through classical pathways, and IL-18 mediates inflammation and activates gasdermin-D protein to induce cellular pyroptosis. Numerous studies have also emphasized the non-classical pathway activated by the NLRP3 inflammasome in chronic kidney disease (CKD) and the inflammasome-independent function of NLRP3. Summary: The NLRP3-targeting inflammasome and its associated pathways have thus been widely studied in models of CKD treatment, but no drug that targets NLRP3 has thus far been approved for the treatment of CKD. Key Messages: We herein reviewed the current interventional methods for targeting the NLRP3 inflammasome in various CKD models, analyzed their underlying mechanisms of action, classified and compared them, and discussed the advantages and follow-up directions of various interventional methods. This review therefore provides novel ideas and a reference for the development of targeted NLRP3-inflammasome therapy in CKD.